India's Contribution to Geomagnetism and Allied Studies in Antarctica-A Review - Sinha, Ashwini K.; Dhar, Ajay; Singh, Anand K.; Behera, Jayanta K.; Gurubaran, S. (My University, 2017)
In this paper, we review the progress in Geomagnetism and allied areas based on the past thirty five Indian Antarctic expeditions and summarize the scientific results obtained in the last decade. Various dynamic processes in the near-Earth space environment, driven by the transient changes in geomagnetic field such as storms and substorms, severely affect the space weather over the Polar Regions. Magnetopsheric substorms lead to the intensification of ionospheric currents and auroral outbursts within the auroral oval, causing energetic charged particles in the auroral region to come down to D-region ionosphere, which is reflected as Cosmic Noise Absorption (CNA) as monitored by imaging RIOmeter at Indian Antarctic station, Maitri (Geog. 70.75o S, 11.73oE; Geom. 66.84oS, 56.29oE). A systematic rapid decline in The Earth’s complex main magnetic field at Maitri (~110 nT/yr) is important for monitoring the evolution of reverse magnetic flux patches due to physical processes occurring in the outer core of the Earth. The Global Electric Circuit (GEC) studies were started to understand the solar-terrestrialrelationship and associated changesin surface weather and the near-earth electrical environment. Schumann resonances (SRs), the AC part of GEC reveal a strong UT variation of amplitude in seasonal as well as yearly time scales. The observed diurnal variation is explained in terms of the dominant thunderstorm activity centered over the three convectively active regions, viz. Asia/Maritime Continent (Indonesia), South America and Africa. The velocity and strain distribution of Schirmarchaer Glacier wasinvestigated during two GPS campaignsin the year 2003 and 2004. The studies indicate that the horizontal velocity is in the range of 1.89-10.88 ma–1 with an average velocity of 6.21 ma–1.
Keywords: Indian Institute of Geomagnetism; IIG; Indian Antarctic Research Stations; Geomagnetism; Global Electric Circuit; GPS; Environmental Magnetic Studies